Estudo da relação entre o Fatty Liver Index e o diagnóstico ultrassonográfico de doença hepática gordurosa não alcoólica - Dias, Nilles Benjamim da Silva (2019)
Introduction: Non-alcoholic fatty liver disease (NAFLD) has been emerging as a worldwide public health problem. It ranges from simple steatosis to steatohepatitis, and may progress to cirrhosis and hepatocellular carcinoma. Ultrasound (US) has been the first option to diagnose NAFLD, but alternative methods, such as the Fatty Liver Index (FLI), have been developed for the diagnosis of the disease. The FLI value defines the presence of hepatic steatosis (HS) if =60 and absence if <30. Objective: To study the relationship between the Fatty Liver Index (FLI) and the diagnosis of NAFLD by US. Methods: We analyzed patients followed at the Liver Steatosis and Nutrition outpatient clinics of the Sergipe University Hospital, from 2017 to 2019, and studied the correlation of the FLI, based on biochemical and anthropometric data, with the diagnosis of NAFLD by US. It was verified using Spearman's rank correlation coefficient. Results: Eighty-eight patients were evaluated, 41 without NAFLD and 47 with NAFLD. The FLI was significantly correlated with the diagnosis of NAFLD by US (p <0.001; r = 0.643), excluding hepatic steatosis (HS) in 100% of patients without NAFLD and confirming in 61.7% of those who had. The mean FLI value in this group was 61.43 ± 21.31 (p <0.001). Conclusion: FLI showed good correlation with NAFLD diagnosed by US, and can be used in places with difficult access to US or in epidemiological studies